2021
DOI: 10.1038/s41598-021-85097-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MicroRNA-205-5p inhibits skin cancer cell proliferation and increase drug sensitivity by targeting TNFAIP8

Abstract: Tumor necrosis factor-α-induced protein 8 (TNFAIP8) is a member of the TIPE/TNFAIP8 family which regulates tumor growth and survival. Our goal is to delineate the detailed oncogenic role of TNFAIP8 in skin cancer development and progression. Here we demonstrated that higher expression of TNFAIP8 is associated with basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and melanoma development in patient tissues. Induction of TNFAIP8 expression by TNFα or by ectopic expression of TNFAIP8 in SCC or melanoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…MiR-205-5p has been linked to cell proliferation and heightened drug responsiveness in basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and melanoma. However, unlike in our investigation, where its influence is anticipated to stem from interactions with the multidrug resistance-associated protein family, miR-205-5p′s suppressive impact in skin cancer is attributed to its targeting of members within the tumor necrosis factor-α family ( Ge et al, 2021 ).…”
Section: Discussionmentioning
confidence: 65%
“…MiR-205-5p has been linked to cell proliferation and heightened drug responsiveness in basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and melanoma. However, unlike in our investigation, where its influence is anticipated to stem from interactions with the multidrug resistance-associated protein family, miR-205-5p′s suppressive impact in skin cancer is attributed to its targeting of members within the tumor necrosis factor-α family ( Ge et al, 2021 ).…”
Section: Discussionmentioning
confidence: 65%
“… 33 Recent research has shown that miR-205-5p increases sensitivity to vemurafenib and induces cell apoptosis in melanoma by down-regulating TNFAIP8. 34 We further proved that miR-205-5p plays an anti-cancer role in melanoma. PAK2 is the target gene of miR-205-5p, and SNHG16 can directly bind to miR-205-5p.…”
Section: Discussionmentioning
confidence: 67%
“…MiR-205-5p has been linked to cell proliferation and heightened drug responsiveness in basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and melanoma. However, unlike in our investigation, where its influence is anticipated to stem from interactions with the multidrug resistance-associated protein family, miR-205-5p′s suppressive impact in skin cancer is attributed to its targeting of members within the tumor necrosis factor-α family (Ge et al, 2021).…”
Section: Discussionmentioning
confidence: 56%